Chia Seed Oil Prevents High Fat Diet Induced Hyperlipidemia and Oxidative Stress in Mice. Issue 4 (4th March 2020) - Han, Kai; Li, Xin‐Yang; Zhang, Ye‐Qi; He, Yong‐Lin; Hu, Rui; Lu, Xiu‐Li; Li, Qi‐Jiu; Hui, Jing
Abstract: Hyperlipidemia is a common cardiovascular disease. At present, the influence of high fat diet (HFD) on this is being explored. Recently, vegetable oils rich in omega‐3 have been reported that can treat hyperlipidemia caused by HFD. However, the effects of chia seed oil (CSO) on HFD‐induced hyperlipidemia and oxidative stress are poorly studied. Hence, in this study, the effects of CSO on hyperlipidemia and oxidative stress induced by HFD in mice are analyzed by various commercial kits, section staining, and protein expression. The results show that CSO decreases body weight and organ index. Meanwhile, CSO reduces serum lipid levels of total cholesterol, triglyceride, and low‐density lipoprotein cholesterol. It can also elevate superoxide dismutase and glutathione peroxidase activities and reduce malondialdehyde content in serum and liver. The results of histopathological analysis prove that CSO improves hepatic steatosis and reduces lipid deposition. Further, the results of western blot demonstrate that CSO upregulates the expression of peroxisome proliferator‐activated receptor alpha and carnitine palmitoyltransferase 1a in the liver. As a result, CSO may be a potential lipid‐lowering oil to prevent and treat HFD‐induced hyperlipidemia and oxidative stress. Practical Applications CSO, as a byproduct of chia seed processing, is a rich source of α‐linolenic acid. This study investigates the effects of CSO on HFD‐induced hyperlipidemia and oxidative stress in mice. It is concluded that dietary CSO can improve the hyperlipidemia in HFD‐induced mice via analysis of lipid parameters, histopathology study of the liver, and lipid metabolism related genes. In addition, supplementation of CSO also can improve the oxidative stress in mice. Therefore, CSO can be used for the prevention of hyperlipidemia and oxidative stress. This research provides a theoretical basis for the comprehensive development and utilization of functional chia seed oil. Abstract : The protective functions of chia seed oil on hyperlipidemia, oxidative stress, and its potential mechanisms in high‐fat diet induced hyperlipidemic mice are investigated.